2022
DOI: 10.1091/mbc.e21-02-0061
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of intracellular neonatal Fc receptor–ligand interactions in primary macrophages using biophysical fluorescence techniques

Abstract: The neonatal Fc receptor (FcRn) is responsible for the recycling of endocytosed albumin and IgG and contributes to their long plasma half-life. We recently identified a FcRn-dependent, recycling pathway from macropinosomes in macrophages (Toh et al, 2019), however, little is known about the dynamics of intracellular FcRn-ligand interactions to promote recycling. Here we demonstrate a multiplexed biophysical fluorescent microscopy approach to resolve the spatiotemporal dynamics of albumin-FcRn interactions in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
(80 reference statements)
1
5
0
Order By: Relevance
“…The acidification of early macropinosomes in Dictyostelium is mediated by WASP regulation of V-ATPase ( Buckley et al, 2016 ) and it is possible that a similar process might occur in mammalian endothelial cells. The emergence of HSA–AF488- and FcRn–mCherry-double-positive tubules was observed after 20–30 min uptake in live BOECs, a period during which acidification had occurred, which would allow for interaction of HSA and FcRn, as we previously demonstrated in BMDMs using biophysical techniques ( Pannek et al, 2022 ). Newly formed macropinosomes then undergo extensive tubulation, which pinches off to form transport carriers that are transported to the periphery of the cell.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…The acidification of early macropinosomes in Dictyostelium is mediated by WASP regulation of V-ATPase ( Buckley et al, 2016 ) and it is possible that a similar process might occur in mammalian endothelial cells. The emergence of HSA–AF488- and FcRn–mCherry-double-positive tubules was observed after 20–30 min uptake in live BOECs, a period during which acidification had occurred, which would allow for interaction of HSA and FcRn, as we previously demonstrated in BMDMs using biophysical techniques ( Pannek et al, 2022 ). Newly formed macropinosomes then undergo extensive tubulation, which pinches off to form transport carriers that are transported to the periphery of the cell.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, FcRn–mCherry showed a similar intracellular distribution as that of endogenous FcRn in BOECs, indicating that the intracellular location was compatible with that of the untagged receptor. Moreover, our previous studies showed that the FcRn–mCherry fusion protein was functionally active in BMDMs ( Pannek et al, 2022 ; Toh et al, 2019 ), indicating that the fluorescently tagged FcRn is correctly located and functional.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations